The use of specific coordination behaviours to manage information processing and task distribution in real and simulated trauma teamwork: an observational study - Liselott Fornander; Maria Garrido Granhagen; Ida Molin; Kati Laukkanen; Karin Björnström Karlsson; Peter Berggren; Lena Nilsson (Scandinavian Journal of Trauma, Resuscitation and Emergency Medicine)
Abstract Trauma teams handle severely injured patients under high temporal demands and need to coordinate and achieve collaborative decision-making and task execution through communication. Specific coordination and communication behaviours are taught in simulation training to enhance team performance. An examination of the role and nature of communication could increase the understanding of educational possibilities and assess the validity of in situ simulation on behalf of communication. Our study aim was to describe the relative use of communication within information and task management, the use of coordinating behaviours, and the use of talking to the room and closed-loop communication in in-real-life trauma assessment and in the simulated domain. We video-recorded all verbal communicative events in four real-world trauma teams and four teams during simulation training. The analysis showed that although the teamwork was task-oriented, information management dominated task management at 64% of all the utterances in-real-life and 68% during simulation. In-real-life, information management was dominated by the codes “request information” (24%) and “confirmation” (21%), whereas “task distribution” (43%) was most frequently used for task management. The only difference between domains was that “give information after request” represented a smaller proportion of the utterances in-real-life compared to simulation (p ≤ 0.001). Talking to the room was primarily used by the teams in both domains to provide information without request and to delegate tasks. Closed-loop communication was used at a low frequency, 3.6% in-real-life, but was significantly higher, 7.7%, in simulation training. We suspect that this outcome reflects the Hawthorne effect. In the simulations, greater information delivery was provided in response to questions, probably accounting for instructor information. Our results may be valuable for research on trauma team behaviour in a simulated environment to draw conclusions about similar activities in-real-life.